Chinese New Year Cultural 2023 introduces Chinese traditional culture - Siti Nurfarmy, Ibrahim (UMPSA, 2023)
PEKAN, 5 January 2023 - Universiti Malaysia Pahang (UMP) organised the Chinese New Year Cultural 2023 programme to strengthen friendships among all ethnic groups in Malaysia.